Women’s Rights to Marriage and Divorce as Enshrined in Islamic Law: Discrimination concerns and issues in Muslim Societies - Islam, Mofidul (International Journal of Psychosocial Rehabilitation, 2020)
Women’s rights towards the provisions of marriage and divorce as enshrined in Islamic law have been the subject to all kinds of controversies, misinterpretation and especially misinformation. In fact, the Quran, the principle authority for all rule and regulations, put women almost equal rights to marriage and divorce with their male counterparts and the rights granted to Muslim women by the Quran are supported and complemented by the ‘authentic’ Hadith of the Prophet Muhammad. Although the Shariat (Islamic law) contains many positive provisions that protect their rights, these provisions have worsened for socio-cultural reasons and the patriarchal system of personal law in the contemporary Muslim societies. This paper analyzes the rights of Muslim women towards the provisions of marriage and divorce as enshrined in Islamic law, and also examines the discrimination concerns and issues against their rights towards the provision of marriage and divorce in Muslim societies.